2008
DOI: 10.1038/bmt.2008.20
|View full text |Cite
|
Sign up to set email alerts
|

Growth and endocrine function in patients with Hurler syndrome after hematopoietic stem cell transplantation

Abstract: Short stature is characteristic of Hurler syndrome, or mucopolysaccharidosis type IH (MPS IH). Hematopoietic stem cell transplantation (HSCT) is used to treat children with MPS IH. While HSCT corrects some of the metabolic features of MPS IH, its effects on growth are not well delineated. We investigated growth in patients with MPS IH after HSCT and described accompanying endocrine abnormalities. A cohort of 48 patients with MPS IH who had received HSCT between 1983 and 2005 were included. The prevalence of sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 33 publications
(42 reference statements)
0
66
0
2
Order By: Relevance
“…Subclinical hypothyroidism with elevated TSH has been reported in patients affected by Fabry disease [lysosomal galactosidase-A deficiency (76,77) and Hurler syndrome/mucopolysaccharidosis type IH (␣-L-iduronidase deficiency (78)], which are more frequent than cystinosis. However, to the best of our knowledge, their underlying thyroid physiopathology has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Subclinical hypothyroidism with elevated TSH has been reported in patients affected by Fabry disease [lysosomal galactosidase-A deficiency (76,77) and Hurler syndrome/mucopolysaccharidosis type IH (␣-L-iduronidase deficiency (78)], which are more frequent than cystinosis. However, to the best of our knowledge, their underlying thyroid physiopathology has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of early bone maturation, growth failure, bone growth plate disorganization, joint contractures, and endocrine abnormalities has been proposed for short stature of patients with various MPS disorders (Polgreen et al 2008;Decker et al 2010;White 2011). Growth hormone (GH)/insulin-like growth factor (IGF-1) deficiency or resistance has been reported in some patients with MPS IH (Hurler syndrome), MPS II, and MPS IIIA and in a rare case of MPS VI (Buyukgebiz et al 1995;Polgreen et al 2008;Gardner et al 2011). However, others have not observed GH/IGF-1, thyroid hormone, or pituitary-hypothalamic insufficiency (in spite of a report of empty pituitary sella) as cause(s) of growth retardation in MPS VI (Von Muhlendahl and Bradac 1975;Borges et al 2003;Decker et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There has been one previous study of growth and endocrine function in this population (Polgreen et al 2008) who also reported evidence of short stature but were unable to comment on final adult height, instead noting that 87% of children had a height <−2SD by 10 years of age. This study did note that 27% had clinical or subclinical hypothyroidism -a finding not replicated in Fig.…”
Section: Discussionmentioning
confidence: 82%